1988
DOI: 10.1177/019262338801600303
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Hyperplasia in Dogs Induced by Oxodipine, a Calcium Channel Blocking Agent

Abstract: Subchronic oral exposure of dogs to Oxodipine, a new calcium channel blocker of the dihydropyridine-type, resulted in dose-related gingival hyperplastic changes. The doses at which an effect was elicited were 24 and 73 times the intended therapeutic dose for man. The effects were first noted after 7 weeks of treatment, and were limited to the high and intermediate dose groups of both sexes. Macroscopically, a generalized enlargement of the maxillary and mandibular facial and lingual gingivae were noted. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, the features of cyclosporin A-induced gingival overgrowth were somewhat different from those induced by nifedipine or phenytoin, i.e., the collagenous component was more redundant in the cyclosporin A-induced gingival overgrowth than in that due to nifedipine or phenytoin ( 13) in rats and dogs (9). It has been reported that oxodipineinduced gingival overgrowth involved bulk enlargement due to fibroblastic proliferation without marked inflammatory cell infiltration in rats (15), or the lamina propria of the hyperplastic gingiva with fibroblastic and capillary proliferation covered by gingival epithelium with elongated rete pegs, acanthosis and parakeratosis in dogs (25). However, these histological changes were not observed in the gingival overgrowth induced by nifedipine in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the features of cyclosporin A-induced gingival overgrowth were somewhat different from those induced by nifedipine or phenytoin, i.e., the collagenous component was more redundant in the cyclosporin A-induced gingival overgrowth than in that due to nifedipine or phenytoin ( 13) in rats and dogs (9). It has been reported that oxodipineinduced gingival overgrowth involved bulk enlargement due to fibroblastic proliferation without marked inflammatory cell infiltration in rats (15), or the lamina propria of the hyperplastic gingiva with fibroblastic and capillary proliferation covered by gingival epithelium with elongated rete pegs, acanthosis and parakeratosis in dogs (25). However, these histological changes were not observed in the gingival overgrowth induced by nifedipine in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, human case reports of this associated side effect have been related to five other agents in this class, including amlodipine (149, 1681, felodipine (921, diltiazem (16, 23, 32, 521, nitrendipine (21) and verapamil (Table 1) (101, 126). Another agent in this group, oxodipine, has been associated with gingival overgrowth in dogs (180) and rats (118). Publications in the scientific literature have validated the association of gingival overgrowth with calcium channel blockers, significantly increasing awareness of this undesirable side effect in the dental community.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Among the other drugs capable to induce a gingival overgrowth, there are some calciutn ion blockers as described in humans (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), dogs (38,39), and rats (40). The most investigated is nifedipine (33)(34)(35)(36)(37), It has been widely used since 1977 for the treatment and prophylaxis of aeute and chronic coronary insufficiency.…”
Section: Discussionmentioning
confidence: 99%